Matrimonial Property Agreement – Importance and Role in Current Society: Array - Niculescu, Liliana (Journal of Danubian Studies and Research, 2020)
In recent years, more and more frequent, problems arise in the face of citizens in defending property rights, including in family relations. A civilized way of regulating the property relationships between spouses during or in the event of marriage is the matrimonial contract or the matrimonial property agreement, also known as a prenuptial contract. Although it is still viewed with scepticism, like many of the novelties that surprise today’s society, the matrimonial property agreement is a legal act whose effects are still perceived with restraint by the majority of couples in Romania. Often considered a conditioning of love when one partner proposes to the other such a Convention, this institution makes a smooth, but safe way in the mentality of those who want to formalize their relationship, or even those they have been already united for many years of marriage. In order to be able to emphasize the importance of regulating this institution, a matrimonial property agreement approach is needed, taking into account the legal principles governing it, its legal character and the specific scope of the agreement.